2013
DOI: 10.2174/15672050113109990146
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Functional Connectivity of the Thalamus in Alzheimer’ s Disease and Mild Cognitive Impairment: A Resting-State fMRI Study

Abstract: Our results revealed disease severity-related alterations of the thalamo-default mode network and thalamocortical connectivity in AD and MCI patients. These results support the hypothesis of network disconnection in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
82
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 79 publications
13
82
1
Order By: Relevance
“…However, there were no brain regions showing altered resting-state functional connectivity with the left thalamus as seed in the OCD patients. Previous researches found that the left and right brain regions with changed VMHC values showed different resting-state functional connectivity pattern [22], and the left and right thalamus may have diverse whole-brain functional connectivity patterns in Alzheimer's disease [45]. Based on the present research results, we infer that the left and right thalamus with changed VMHC values may also have different functional connectivity pattern at resting-state in OCD patients.…”
Section: Research Ping LIsupporting
confidence: 65%
“…However, there were no brain regions showing altered resting-state functional connectivity with the left thalamus as seed in the OCD patients. Previous researches found that the left and right brain regions with changed VMHC values showed different resting-state functional connectivity pattern [22], and the left and right thalamus may have diverse whole-brain functional connectivity patterns in Alzheimer's disease [45]. Based on the present research results, we infer that the left and right thalamus with changed VMHC values may also have different functional connectivity pattern at resting-state in OCD patients.…”
Section: Research Ping LIsupporting
confidence: 65%
“…Such overactivation patterns have been previously observed in MCI and have been associated with compensatory mechanisms against gray matter loss; for example in the hippocampus for memory (Dickerson et al, 2005a(Dickerson et al, , 2005bHämäläinen et al, 2007) and prefrontal cortex for verbal learning (Clément and Belleville, 2010). Interestingly, previous studies have shown volume reduction in thalamus (Chen and Herskovits, 2006;Karas et al, 2004;Pennanen et al, 2005) and abnormal resting state connectivity with other brain areas (Cai et al, 2015;Wang et al, 2012;Zhou et al, 2013) for MCI patients. Further, volume reductions in thalamus and putamen, have been shown to predict cognitive decline in ageing and conversion to Alzheimer′s disease (de Jong et al, 2008).…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, bilateral GM loss of thalamus characterizing our aMCI sample might account for impaired alpha connectivity between anterior and posterior regions of the brain, likely due to synaptic dysfunction or synaptic loss of thalamocortical neurons. This hypothesis is supported by studies showing amyloid deposits and neurofibrillary tangles in the thalamus of AD patients (Rudelli et al 1984;Masliah et al 1989;Braak and Braak 1991) together with significant GM loss (Karas et al 2004) that further correlated with impaired cognitive functioning (de Jong et al 2008), and by studies showing altered patterns of functional connectivity between thalamus and precuneus in aMCI subjects (Cantero et al 2009a;Wang et al 2012;Zhou et al 2013).…”
Section: Brain Struct Functmentioning
confidence: 82%